2016
DOI: 10.1016/j.engappai.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Identifying user habits through data mining on call data records

Abstract: In this paper we propose a framework for identifying patterns and regularities in the pseudoanonymized Call Data Records (CDR) pertaining a generic subscriber of a mobile operator. We face the challenging task of automatically deriving meaningful information from the available data, by using an unsupervised procedure of cluster analysis and without including in the model any apriori knowledge on the applicative context. Clusters mining results are employed for understanding users' habits and to draw their char… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 43 publications
(40 reference statements)
0
20
0
Order By: Relevance
“…• Internet traffic, including activity on social media and data from search engines • Movement-related data, and different visualizations, including pictures, video, BIM models and maps • Physical environment, typically from different types of sensors • Commercial activity, the use of payment services and consumption patterns New types of data open many possibilities for the analysis of transport measures (Barabino et al, 2014;Bianchi, Rizzi, Sadeghian, & Moiso, 2016). A significant portion of Big Data is geospatial data, generated from sources such as mobile devices and RFID sensors.…”
Section: New Types Of Datamentioning
confidence: 99%
“…• Internet traffic, including activity on social media and data from search engines • Movement-related data, and different visualizations, including pictures, video, BIM models and maps • Physical environment, typically from different types of sensors • Commercial activity, the use of payment services and consumption patterns New types of data open many possibilities for the analysis of transport measures (Barabino et al, 2014;Bianchi, Rizzi, Sadeghian, & Moiso, 2016). A significant portion of Big Data is geospatial data, generated from sources such as mobile devices and RFID sensors.…”
Section: New Types Of Datamentioning
confidence: 99%
“…CDRs are generated by phone communication activities and contain relevant information about the activity (e.g., caller/callee, time, duration) and the location of the cell phone tower that handles the communication (Zhao et al, 2016). Studies have shown that CDR data can be used to study habits and mobility patterns of mobile users (Bianchi et al, 2016;Zhao et al, 2016), to study user movements (Leo et al, 2016), and to calculate commuting matrices with a very high level of accuracy (Frias-Martinez, et al, 2012). Studies have also looked at utilizing mobile data to estimate intra-city travel time (Kujala, Aledavood, & Saramäki, 2016) and have shown that mobile data could be employed as a real-time traffic monitoring tool (Järv et al, 2012).…”
Section: Mobile Phone Data and Alternative Technologiesmentioning
confidence: 99%
“…With pseudo-anonymised data (i.e., the ID is replaced with a code), the record must be pre-processed to reduce probability of re-identification. A common procedure is to decrease time resolution or increase space granularity (Bianchi et al, 2016). Norwegian Law states that collected personal information should only be used for the specific purpose for which it was originally collected (Drageide, 2009).…”
Section: Mobile Phone Data and Alternative Technologiesmentioning
confidence: 99%
“…These data have been analysed to investigate applications in areas such as transportation planning (Di Lorenzo et al, 2016), user behaviour (Bianchi et al, 2016), public health (Oliver et al, 2015), the spatial spread of diseases such as cholera (Bengtsson et al, 2015) or population displacement after a major disaster (Wilson et al, 2016).…”
Section: Passive Non-framework Datamentioning
confidence: 99%